Olajtartalmú veszélyes hulladék előkezelő vákuum bepárló technológiával történő fejlesztésének munkavédelmi kérdései - Zákányiné Mészáro, Renáta; Árvai, Károly; Zákányi, Balázs (Multidiszciplinaris Tudomanyok, 2024)
In our work, we have reviewed and examined the management practices of older technologies for the treatment of oily waters, oily sludges and emulsions in terms of their potential for improvement. We found that the technology used is not suitable for emulsion degradation. Based on a review of some of the technologies used in international and national practice, we have selected the emulsion degradation equipment that can be proposed for the treatment of emulsions and that can be optimally integrated into the older technology. The occupational safety and chemical risks of the selected vacuum evaporation technology were analysed and evaluated in comparison with the risks of the applied technology. It was concluded that the proposed development of the technology does not pose any additional occupational safety and health risks to workers.